Simultaneous Adsorption And Degradation Of Methylene Blue Using Magnetic Carbon Nanotubes - Lee, Ee Chia (2020)
Magnetic multiwalled carbon nanotubes (MWCNTs-Fe3O4 nanocomposites) synthesized by solvent free direct doping method, was subjected for the removal of cationic methylene blue (MB) dyes. The functional groups, phase structure, surface morphology, surface area and thermal stability of the synthesized nanocomposites were then characterized by various physicochemical characterizations such as Fourier transform infrared (FTIR), X-ray powder diffraction (XRD), scanning electron microscopy coupled with energy dispersive X-ray (SEM-EDX), Braunauer-Emmett-Teller (BET) and thermogravimetric analysis (TGA). FTIR analysis confirmed the presence of carboxylic groups in the acid treated MWCNTs as well as the successfully doping of Fe3O4 nanoparticles onto MWCNTs. Next, XRD and SEM-EDX analysis further supported that the synthesized nanocomposites consisted of both hexagonal graphite structure of MWCNTs and the inverse spinel structure of Fe3O4 nanoparticles. In addition, BET analysis indicated that the surface area of the synthesized MWCNTs-Fe3O4 nanocomposites increased significantly as compared to the raw and acid treated MWCNTs. TGA analysis also showed that the MWCNTs-Fe3O4 nanocomposites to possess high thermal stability. Design Expert simulation was employed to determine the effects of various process parameters in the adsorption and degradation of MB. The process parameters studied included pH (2 – 10), initial MB concentration (10 – 50 mg/L), MWCNTs-Fe3O4 nanocomposites dosage (10 – 30 mg) and H2O2 concentration (5 – 20 mmol/L). The optimum reaction condition was then acquired via the response surface methodology (RSM) associated with central composite design (CCD). Results showed that an average optimum percentage of MB degradation of 95.92 % can be achieved under the following reaction conditions: pH of 5.86, initial MB concentration of 32.22 mg/L, MWCNTs-Fe3O4 nanocomposites dosage of 27 mg and H2O2 concentration of 13.02 mmol/L.